2019
DOI: 10.1186/s12935-019-0897-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-369-3p participates in endometrioid adenocarcinoma via the regulation of autophagy

Abstract: Background The aim of this study is to examine miRNA profiling and miR-369-3p participates in endometrioid adenocarcinoma (EEC) via the regulation of autophagy. Methods EEC and its adjacent normal tissues were obtained from 20 clinical patients after surgery. MiRNA profiling was performed using next generation sequencing (NGS) and was validated with quantitative real time PCR (qRT-PCR). qRT-PCR was also employed to measure miR-369-3p and autophagy-related protein 10 (AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…lncRNA is a competitive endogenous RNA with a miRNA recognition element, which can compete with mRNAs for the same miRNA response element, thus inhibiting the binding of miRNAs to mRNAs and affecting the regulatory effect of miRNAs on target genes ( 26 ). miR-369-3p expression has been found to be decreased in endometrioid adenocarcinoma tissues and miR-369-3p overexpression suppresses cell proliferation and migration in endometrioid adenocarcinoma ( 27 ). miR-369-3p expression has been shown to be notably increased in Hirschsprung's disease and the dysregulation of miR-369-3p has been shown to decrease the proliferation and migration of the SH-SY5Y and 293T cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA is a competitive endogenous RNA with a miRNA recognition element, which can compete with mRNAs for the same miRNA response element, thus inhibiting the binding of miRNAs to mRNAs and affecting the regulatory effect of miRNAs on target genes ( 26 ). miR-369-3p expression has been found to be decreased in endometrioid adenocarcinoma tissues and miR-369-3p overexpression suppresses cell proliferation and migration in endometrioid adenocarcinoma ( 27 ). miR-369-3p expression has been shown to be notably increased in Hirschsprung's disease and the dysregulation of miR-369-3p has been shown to decrease the proliferation and migration of the SH-SY5Y and 293T cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, increased ATG10 expression is associated with lymph node metastasis and lymphovascular invasion [ 58 ]. ATG10 is a target gene of miR-369-3p, which inhibits cell proliferation and migration by targeting cancer cells via autophagy in endometrioid adenocarcinoma [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu P. et al have reported that miR-369-3p, similarly to miR-365, can also act as a tumor suppressor, inducing apoptosis and inhibiting cell migration by targeting ATG10 in endometrioid adenocarcinoma [ 110 ]. On the contrary, miR-200, miR-296-5p and miR-654 have been described in different studies as oncomirs [ 86 , 111 , 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%